2015
DOI: 10.7202/1033845ar
|View full text |Cite
|
Sign up to set email alerts
|

La reconnaissance émotionnelle faciale : validation préliminaire de stimuli virtuels dynamiques et comparaison avec les Pictures of Facial Affect (POFA)

Abstract: Bien que des photographies d’expressions émotionnelles faciales soient couramment utilisées pour étudier le traitement des informations affectives, les ensembles de stimuli actuels comportent différentes limites méthodologiques. Dans la perspective d’améliorer la validité écologique des travaux sur la reconnaissance émotionnelle faciale (REF), l’étude propose un nouvel ensemble de stimuli dynamiques constitué de personnages virtuels exprimant les six émotions fondamentales à différentes intensités. La validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Most notable in the present study is the strong negative effect of face masks on the recognition of disgust. Adult participants in an earlier, very similar study ( Carbon, 2020 ) also showed a pronounced decline of performance for this specific emotion; however, adult participants mainly misperceived disgust as anger—reflecting a common finding (see, e.g., Cigna et al., 2015 )—but they did not confuse disgust with sadness as the kids did. We do not yet know the base of this effect, but it points to the relevance of such findings for children’s everyday life: Face masks cover a large part of the face, and only so they seem to be effective in mitigating the viral load entering the respiratory passages through the mouth and the nose.…”
Section: Discussionmentioning
confidence: 73%
“…Most notable in the present study is the strong negative effect of face masks on the recognition of disgust. Adult participants in an earlier, very similar study ( Carbon, 2020 ) also showed a pronounced decline of performance for this specific emotion; however, adult participants mainly misperceived disgust as anger—reflecting a common finding (see, e.g., Cigna et al., 2015 )—but they did not confuse disgust with sadness as the kids did. We do not yet know the base of this effect, but it points to the relevance of such findings for children’s everyday life: Face masks cover a large part of the face, and only so they seem to be effective in mitigating the viral load entering the respiratory passages through the mouth and the nose.…”
Section: Discussionmentioning
confidence: 73%
“…When expressive, the avatar progressively changed reaching an expressivity peak (apex) at 10.5 s (i.e., morphing technique), whereas the avatar remained inexpressive during whole 10.5 s for the neutral expression. Creation of those stimuli was performed using an approach similar to Cigna et al (2015) . The avatars’ faces were generated using FaceGen Artist Pro (Singular Inversions Inc., Toronto, ON, Canada) and Daz Studio software (Daz Productions Inc., Salt Lake City, UT, United States), and their animation and shading were performed using Autodesk Mudbox (Autodesk Inc., San Rafael, CA, United States) and Unity Software (Unity Technologies Inc., San Francisco, CA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Despite being a complex process, the capacity for processing face information is of utmost importance for social interaction (O'Reilly et al, 2016) and seems to be relatively universal (Cigna et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of consistency across studies may also result from the nature of the stimulus materials used. Although some studies have used stimuli based on real human models (actors or nonactors), others included avatars or computer edited faces (e.g., Cigna et al, 2015;Gold et al, 2013;Horstmann & Ansorge, 2009). Yet some authors (e.g., Sato, Fujimura, & Suzuki, 2008) suggest that the use of Breal people^is more suitable when using dynamic stimuli.…”
Section: Static Versus Dynamic Facial Expressionsmentioning
confidence: 99%